Reforms of China's state-owned enterprises - an investment perspective. - Chua, Han Yunn. (2008)
This research hopes to equip potential investors with the necessary basic understanding of the issues involved with particular emphasis given to labour and social security issues. Insightful interviews with two legal counsels and an experienced SOE investor uncovered many interesting practical issues and suggested solutions.